An overview of the methamphetamine effect on male sexual behavior and reproductive system - Mihalčíková, L; Šlamberová, R (Physiological research, 2023)
Drug addiction and its effect on the behavior and development of children has become a serious problem in our society. Methamphetamine (MA) is one of the most abused psychostimulants in the Czech Republic, and its abuse is rising worldwide. Previous studies have demonstrated the adverse long-term effects of maternal drug abuse on rat offspring. However, the father's contribution as a parent and donor of half of the genetic information is unclear. Previous studies of other psychostimulant drugs indicate that long-term application of MA to adult male rats may induce changes in their reproductive system and lead to changes in rat pup functional and behavioral development. Therefore, the present review aimed to investigate the effect of MA administration on reproductive toxicity and sexual behavior of adult male rats, as well as the impact of paternal MA exposure on behavioral development and locomotor activity in rat offspring.
Keywords: chování zvířat; Humans; zpožděný efekt prenatální expozice; Sexual Behavior; dítě; Child; pohlavní orgány; Female; Methamphetamine; dospělí; krysa rodu Rattus; lidé; zvířata; stimulanty centrálního nervového systému; potkani Wistar; methamfetamin; Adult; ženské pohlaví; Rats, Wistar; Male; Rats; Animals; Prenatal Exposure Delayed Effects; Central Nervous System Stimulants; mužské pohlaví; Genitalia; Behavior, Animal; sexuální chování